2005
DOI: 10.5005/jcdp-6-3-40
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitative Management Offered Nigerian Localized and Generalized Aggressive Periodontitis Patients

Abstract: This paper highlights the typical clinical features of aggressive periodontitis (formerly known as juvenile periodontitis in the South Western region of Nigeria), the attending psychological effect following tooth loss, and the rehabilitative management offered which included periodontal therapy, psychotherapy, and prosthetic replacement of the missing teeth. The psychotherapy is the main distinguishing treatment in this study from previously reported modes of management of this disease entity.Subjects were fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…[8] The problem, however, is that some of the nine patients seen in one of the study centers reported previous dental visits where extractions had been performed without proper management of AgP.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The problem, however, is that some of the nine patients seen in one of the study centers reported previous dental visits where extractions had been performed without proper management of AgP.…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapy has a very positive effect on the attitude and behaviour of the patient and should be continued depending on the psychological status of the patient. A recent study reported that psychotherapy offered to a generalised aggressive periodontitis patient had a positive psychological effect that restored their ability to socialise in their environment, contributing to their positive experiences in life, which enhanced the role of special psychological care in a multidisciplinary approach in the treatment of a case of generalised aggressive periodontitis 4 5Learning points

Generalised aggressive periodontitis causes rapid destruction of the tooth supporting structures leading to substantial loss of alveolar bone and teeth.

Early diagnosis plays an important role in saving a substantial amount of alveolar bone and teeth.

The treatment plan for generalised aggressive periodontitis should also include a psychological approach.

…”
Section: Discussionmentioning
confidence: 99%
“…Globally there is a paradigm shift in the population, as the proportion of older people is growing further than that of any other group . The older people, therefore, are at a greater risk of oral diseases such as periodontal diseases and tooth loss, which are of high prevalence among them in Nigeria . In the recent past, studies had also shown that elderly population were retaining their teeth more than before .…”
Section: Introductionmentioning
confidence: 99%
“…The older people, therefore, are at a greater risk of oral diseases such as periodontal diseases and tooth loss, which are of high prevalence among them in Nigeria . In the recent past, studies had also shown that elderly population were retaining their teeth more than before . Tooth loss without replacement can lead to adverse effects in the remaining dentition as well as negative impact on the quality of life of elderly individuals .…”
Section: Introductionmentioning
confidence: 99%